Bahasa Inggris - Agneso Feronika Limbong; Nurhayati Sitorus; Srisofian Sianturi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2026)
This study aims to analyze the types of illocutionary acts used by the main character in the movie Heads of State (2025) and to identify the dominant type of illocutionary act found in the movie. This research is based on pragmatic theory, particularly speech act theory proposed by Austin (1962) and further developed by Searle (1979). The study uses a qualitative descriptive method to analyze the utterances produced by the main character in the movie. The data were obtained from the main character’s dialogue in several selected scenes of Heads of State (2025). The data were collected by watching the movie repeatedly, identifying the relevant utterances, and transcribing the dialogues. The analysis of the data was conducted using Searle’s classification of illocutionary acts, which consists of assertive, directive, commissive, expressive, and declarative acts. The findings reveal that all five types of illocutionary acts are found in the main character’s utterances in the movie. These types include assertive, directive, commissive, expressive, and declarative acts. Among these types, assertive illocutionary acts are the most dominant type used by the main character. Assertive acts are frequently used by the character to convey information, express beliefs, provide explanations, and describe situations occurring in the story. The dominance of assertive acts indicates that the main character often functions as a source of information in the development of the movie’s narrative. Keywords: assertive; Heads of State (2025); illocutionary acts; pragmatics; speech acts.